2021
DOI: 10.3390/bs11100140
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Posttraumatic Stress Disorder after Terrorist Attacks: A General Review of the Literature

Abstract: Terrorism, though not well-defined, is a violent act that has been shown to have longstanding effects on the mental health of those who witness it. The aim of this general literature review is to explore the effect that terrorism has on posttraumatic stress disorder (PTSD), major depressive disorder (MDD) and anxiety disorders, as well as the bio-psycho-social determinants that mediate its impact. This paper describes the prevalence, risk factors, protective factors, common presentations and interventions iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 85 publications
1
16
1
Order By: Relevance
“…Indeed, attack-related psychological disorders such as PTSD change over time, and improving knowledge on mental health evolution is needed [11]. In addition, intentional events such as terrorism lead to a greater persistence of PTSD symptoms over time compared to unintentional events [12]. The bulk of studies have shown an increase in PTSD symptoms among FR, such as among FR to the 2001 World Trade Centre (WTC) terrorist attacks, with PTSD prevalence of 12.1% in wave 1 (2-3 years after the attacks) and 19.5% in wave 2 (5-6 years after the attacks).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, attack-related psychological disorders such as PTSD change over time, and improving knowledge on mental health evolution is needed [11]. In addition, intentional events such as terrorism lead to a greater persistence of PTSD symptoms over time compared to unintentional events [12]. The bulk of studies have shown an increase in PTSD symptoms among FR, such as among FR to the 2001 World Trade Centre (WTC) terrorist attacks, with PTSD prevalence of 12.1% in wave 1 (2-3 years after the attacks) and 19.5% in wave 2 (5-6 years after the attacks).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, floods in Western Europe killed more than 200 people and destroyed many buildings and infrastructure in Germany, Belgium, Luxembourg, and the Netherlands [ 2 ]. General practitioners (GPs) are also confronted with these crises on a personal and professional level, both in the context of early acute stress and longer-term problems such as posttraumatic stress disorder (PTSD) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…When we look more specifically at the consequences of terrorist attacks, we know from previous reviews that their impact on the affected can be extensive. Among directly exposed (direct witnesses and those injured in the event), a large minority develops significant levels of posttraumatic stress symptoms ( García-Vera et al, 2016 ; Stene et al, 2016 ; Rigutto et al, 2021 ), including PTSD. Other psychological consequences, such as (major) depression or anxiety disorders are also common among directly involved victims ( Whalley and Brewin, 2007 ; Salguero et al, 2011 ; Dyb et al, 2014 ; Stene et al, 2016 ; Lowell et al, 2018 ; Rigutto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among directly exposed (direct witnesses and those injured in the event), a large minority develops significant levels of posttraumatic stress symptoms ( García-Vera et al, 2016 ; Stene et al, 2016 ; Rigutto et al, 2021 ), including PTSD. Other psychological consequences, such as (major) depression or anxiety disorders are also common among directly involved victims ( Whalley and Brewin, 2007 ; Salguero et al, 2011 ; Dyb et al, 2014 ; Stene et al, 2016 ; Lowell et al, 2018 ; Rigutto et al, 2021 ). In addition, victims often suffer from physical complaints (e.g., Van den Berg et al, 2005 ; Yzermans et al, 2009 ; Stene et al, 2016 ; Glad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation